Предмет: Алгебра, автор: marivakulchuk

дпа, упростить выражение

Приложения:

Ответы

Автор ответа: maksimcat
2
(\frac{x-2y}{ x^{2} +2xy} - \frac{x+2y}{ x^{2} -2xy} ): \frac{4y^2}{4y^2-x^2} = \\  \\ (\frac{x-2y}{ x(x+2y)} - \frac{x+2y}{x(x-2y)} )* \frac{4y^2-x^2}{4y^2} = \\  \\  \frac{(x-2y)^2-(x+2y)^2}{x(x+2y)(x-2y)} * \frac{4y^2-x^2}{4y^2} = \\  \\ \frac{x^2-4xy+4y^2-x^2-4xy-4y^2}{x(x+2y)(x-2y)} * \frac{4y^2-x^2}{4y^2} = \\  \\  \frac{-8y}{x^2-4y^2} * \frac{4y^2-x^2}{4y^2} =  \frac{2}{y}  \\  \\

Похожие вопросы
Предмет: Физика, автор: gulgocaeva4